Organizational Meeting Orientation: Setting the Stage for Team Success or Failure Over Time - Mroz, Joseph E.; Landowski, Nicole; Allen, Joseph Andrew; Fernandez, Cheryl (Frontiers in Psychology, 2019)
Teams are an integral tool for collaboration and they are often embedded in a larger organization that has its own mission, values, and orientations. Specifically, organizations can be oriented toward a variety of values: learning, customer service, and even meetings. This paper explores a new and novel construct, organizational meeting orientation (the set of policies and procedures that promote or lead to meetings), and its relationship to perceived team meeting outcomes and work attitudes. An organization’s policies, procedures, and overall orientation toward the use of team meetings—along with the quality and perceived effectiveness of those meetings—set the stage for how teams develop and collaborate. Across two studies, we demonstrate that perceptions of an organization’s orientation toward meetings is associated with the perceived quality and satisfaction of team meetings, along with work engagement and intentions to quit. Employees who feel meetings lack purpose or are overused tend to be less engaged with their work and more likely to consider leaving the organization. Based on the findings, we conclude with a robust discussion of how meeting orientation may set the stage for team interactions, influencing how their team operates over time on a given project or series of projects. An organization’s orientation toward meetings is a new construct that may exert an influence on team dynamics at the organizational level, representing a factor of the organization that affects how and when teams meet and collaborate.